Повышение эффективности работы технологического оборудования при проведении буровзрывных работ на карьере строительного камня - Казанович, К. А.; Воропаева, Д. К. (БНТУ, 2020)
The main types of equipment for carrying out drilling and blasting operations in a building stone quarry are considered: shot holes drills in rocks, as well as machines for mechanized loading of explosives in the production of massive explosions in quarries. The features of the application of technological schemes for switching charges in the production of mass explosions at mining enterprises are given. The main methods of crushing oversized materials after carrying out massive explosions on a pit bench are considered.